Makna berhadapan dengan notaris pada akta risalah Rapat Umum Pemegang Saham yang diselenggarakan secara elektronik dalam Perspektif Peraturan Perundang-undangan - Yogha Octhanio Pratama; Yetniwati Yetniwati; Dwi Suryahartati (LITERATUS, 2022)
This study aims to analyze, find out and then explain the concept of dealing in making the minutes of the General Meeting of Shareholders held electronically. Methods This research uses a normative juridical method. The results of this study are the differences in the views of experts in viewing the expansion of the meaning of "dealing with a Notary" which physically can be carried out through electronic media in the UUJN, this raises doubts among Notaries in carrying out their Duties and Authorities in carrying out their duties, because it can resulting in the strength of proof of the product of the E-GMS minutes of deed that he made. Hierarchically, the POJK legislation does not necessarily shift the provisions in the UUJN which have the status of a law and have a higher position. Ideally, the E-GMS mechanism is regulated in a Government Regulation (PP) whose basic regulation is Law Number 40 of 2007 concerning Limited Liability Companies. Lex Generalis.